Isolation of Dermatophytes among Primary School Pupils in Akungba Akoko, Ondo State - Folorunso, V. T. (British Journal of Healthcare and Medical Research, 2023)
Dermatophytic infection remain a public health problem among children globally and particularly in Nigeria. Hence, A cross sectional study was conducted to investigate the prevalence of dermatophytic infection among primary school children in Akungba Akoko, a part of Ondo State, Nigeria. A total of one hundred and forty-five (145) children were included in the study. Sixty-five (65) of the study population (145 pupils) was infected with dermatophytosis. The nails, skin scrappings and hair samples of participant were collected aseptically randomly. The samples were appropriately cultured, examined microscopically, and characterized using molecular methods. The study revealed that the prevalence of dermatophytic infection among school children was 44.82%. Furthermore, the study showed higher prevalence and distribution of dermatophytosis in boys (69.23%) than in girls (30.77%). Among the isolated dermatophytes, M. audounii had the highest frequency of 32.20% while M. gypseum had the least frequency of 4.61%. The study also revealed that school children of age group 1-5 and 6–10 years appeared more susceptible to dermatophytic infection. In respect to infection site, majority of the identified dermatophytes were isolated from the scalp (93.85%) compared with those that occurred as skin lesions (6.15%). From this findings, the prevalence of dermatophytes among school children in Akungba akoko area of Ondo state demands an urgent public health measures from concerned personnels. Meanwhile, a survey of larger population size is recommended to validate the findings from this study.